Persepsi Dan Preferensi Pengguna Terhadap Prasarana dan Perlengkapan Jalan di Kawasan Lapangan Puputan Margarana - Prabowo, Xand Conery; Pradnyawathi, Ni Luh Made; Asmiwyati, I Gusti Agung Ayu Rai (Jurnal Arsitektur Lansekap, 2021)
User perceptions and preferences on road infrastructure and equipment at region of Lapangan Puputan Margarana. Denpasar is one of the most populated city in Bali. The density is caused mainly by the rapidly increasing population that affects the traffic growth in Denpasar. The Puputan Margarana Square has been the venue for entertainment, recreation and sport activities for the people of Denpasar. Being the meeting point of several streets, has made Puputan Margarana quite crowded that it needs to be balanced and equipped with sufficient supporting roads and facilities in the area. The purpose of the research is to measure the perception and preference of the user on the safety and comfort of the facilities in the areas (Jalan Ir. H. Juanda, Jalan Basuki Rahmat, dan Jalan Kusuma Atmaja). The research method used was survey method by the technique in this research was a direct observation, interviews and questionnaires. Based on the research, it was revealed that the perception of the users on the safety and comfort of the accessibility and circulation, sidewalks, crossing area, parking area and other road equipment in the Puputan Margarana square are considered to be sufficiently safe and comfortable. User’s preference indicates that further arrangement and addition of several supporting facilities is still required. The research result is a recommendation on the several street facilities and equipment and also hoped to be a reference information for the related institutions.